2012
DOI: 10.1128/aem.01200-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence and Mutational Analysis of Plant-Growth-Promoting Bacterium Agrobacterium tumefaciens CCNWGS0286 Isolated from a Zinc-Lead Mine Tailing

Abstract: The plant-growth-promoting bacterium Agrobacterium tumefaciens CCNWGS0286, isolated from the nodules of Robinia pseudoacacia growing in zinc-lead mine tailings, both displayed high metal resistance and enhanced the growth of Robinia plants in a metal-contaminated environment. Our goal was to determine whether bacterial metal resistance or the capacity to produce phytohormones had a larger impact on the growth of host plants under zinc stress. Eight zinc-sensitive mutants and one zinc-sensitive mutant with redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 53 publications
(48 reference statements)
0
40
0
Order By: Relevance
“…Genome sequences were then annotated with the MicroScope platform (Vallenet et al 2013) (Goodner et al 2001;Wood et al 2001;Li et al 2011;Ruffing et al 2011;Wibberg et al 2011;Hao, Lin, et al 2012;Hao, Xie, et al 2012). These 22 genomes covered 10 closely related but genomically differentiated species (G1 to G9 and G13), with up to five isolates per species.…”
Section: Bacterial Culture Experimentsmentioning
confidence: 99%
“…Genome sequences were then annotated with the MicroScope platform (Vallenet et al 2013) (Goodner et al 2001;Wood et al 2001;Li et al 2011;Ruffing et al 2011;Wibberg et al 2011;Hao, Lin, et al 2012;Hao, Xie, et al 2012). These 22 genomes covered 10 closely related but genomically differentiated species (G1 to G9 and G13), with up to five isolates per species.…”
Section: Bacterial Culture Experimentsmentioning
confidence: 99%
“…Even the most susceptible plants exposed to large pathogen populations will not develop diseases unless environmental conditions are favourable. As a consequence, bacteria have evolved to monitor environmental cues, such as temperature, light, water deficit, soil and rhizosphere pH, heavy metals and pesticides (Silver and Phung le, 2005;Efetova et al, 2007;Jing et al, 2007;Oberpichler et al, 2008;Hao et al, 2012;Haldar and Sengupta, 2015;Wei et al, 2015). In addition, soil texture and moisture content also affect root exudation and, therefore, modulate plantmicrobe interactions (Haldar and Sengupta, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that several metal resistance determinants in rhizobia were required for effective symbiosis formation or could enhance phytohormone indole-3-acetic acid (IAA) production (20,21,23). However, the exact molecular mechanisms explaining how the rhizobial metal resistance determinants interact with the synthesis of growth-promoting substances, nodulation and nitrogen fixation, and, ultimately, phytoremediation processes still remain largely elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous greenhouse studies, the metal resistance determinants in rhizobia were shown to affect the functional symbiosis formation under heavy metal stress (20,21,23). Therefore, the Cu-sensitive mutant (ΔcueO) and three mutants that were both Cu and Zn sensitive (ΔyedYZ, ΔcusA-like, and ΔfixH-like) were selected for further study of the effects of the metal resistance determinants on root nodule symbiosis.…”
Section: Resultsmentioning
confidence: 99%